Characteristics of idiopathic REM sleep behavior disorder and that associated with MSA and PD - A. Iranzo; Joan Santamaría; David B. Rye; Francesc Valldeoriola; M. J. Martí; Esteban Muñoz; Isabel Vilaseca; E. Tolosa (2005)
Objective: To compare the clinical and video-polysomnographic (VPSG) characteristics of idiopathic REM sleep behavior disorder (RBD) vs the RBD seen in multiple system atrophy (MSA) and Parkinson disease (PD). Methods: Clinical features and VPSG measures were evaluated in 110 consecutive nondemented subjects (26 MSA, 45 PD, and 39 idiopathic RBD) free of psychoactive medications referred for suspected RBD to our sleep unit over a 5-year period, with extended follow-up (mean 26.9 ± 21.3 months). Results: Across the three groups studied, logistic regression analysis demonstrated that there were no differences in the quality of RBD symptoms (e.g., nature of unpleasant dream recall or behaviors witnessed by bed partners), most PSG variables, abnormal behaviors captured by VPSG, and clinical response to clonazepam. When compared to subjects with PD, however, patients with MSA had a significantly shorter duration of disease, a higher REM sleep without atonia percentage, a greater periodic leg movement index, and less total sleep time. Subjects with idiopathic RBD, as compared to those with either MSA or PD, were more often male, had greater self-reported clinical RBD severity, and were more often aware of their abnormal sleep behaviors. Conclusions: REM sleep behavior disorder (RBD)-related symptoms and neurophysiologic features are qualitatively similar in RBD subjects with the idiopathic form, multiple system atrophy (MSA), and Parkinson disease (PD). Polysomnographic abnormalities associated with RBD in the setting of MSA are greater than in PD, suggesting a more severe dysfunction in the structures that modulate REM sleep.